Effectiveness of Monetary Policy Channels: Insights from Four Emerging Economies - Senturk, Ismail; Ali, Amjad (Journal of Business and Economic Options, 2021)
The focus of this paper is to delve into the monetary policy transmission mechanisms in four emerging economies: Chile, Russia, Mexico, and Turkey. Using a vector autoregressive model, the study aims to uncover how monetary policy actions impact key economic variables in these countries. A significant finding of the empirical study is the effectiveness of the exchange rate channel in Turkey's monetary policy transmission mechanism. This suggests that changes in monetary policy, particularly interest rate adjustments, have a notable impact on the exchange rate in Turkey, which in turn influences various aspects of the economy. However, the study also reveals that the exchange rate channel's effectiveness is relatively low in Russia, Chile, and Mexico compared to Turkey. This implies that while changes in monetary policy may still influence exchange rates in these countries, the magnitude of this impact is not as significant as observed in Turkey. Moreover, the interest rate channel, which involves changes in interest rates affecting borrowing, lending, and investment decisions, is found to be limited in all four countries. This suggests that monetary policy actions aimed at adjusting interest rates may have only a modest impact on economic variables in these economies. Overall, these findings shed light on the nuances of monetary policy transmission mechanisms in emerging economies, highlighting the varying degrees of effectiveness across different channels and countries. Understanding these dynamics is crucial for policymakers in designing and implementing monetary policies that effectively support economic stability and growth in these nations.